A Study of the Organisational Culture of a Property Developer in Singapore - Ong, Kung Yew (2006)
Corporate culture can have a significant impact on a firm's long-term economic performance. Firms with a culture that emphasised all key managerial constituencies and leadership from managers at all levels out-performed firms that did not. Corporate cultures that inhibit strong long-term financial performance are not rare; they develop easily. Once such culture exist, they can be enormously difficult to change because they are often invisible to the people involved. Although tough to change, corporate cultures can be made more performance enhancing; it requires time, leadership and a realistic vision.